Pengaruh Green Marketing, Servicescape, dan Service Quality Terhadap Loyalitas Pelanggan (Studi Kasus pada Retrorika Coffee Bar and Resto di Kota Batu) - Kusumawardani, Parawansa Galuh; Khalikussabir, Khalikussabir; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of green marketing, servicescape, and service quality on customer loyalty at Retrorika Coffee Bar and Resto. These three variables are considered strategic elements relevant to customer loyalty, yet they have rarely been comprehensively studied in the context of local cafés. This study employs a quantitative approach using purposive sampling techniques. The sample consists of 80 respondents who are customers of Retrorika Café residing in Malang and Batu. Research data were collected through the distribution of questionnaires and analyzed using multiple linear regression techniques with the assistance of SPSS 29.0. The results indicate that, simultaneously, green marketing, servicescape, and service quality significantly influence customer loyalty. Partially, green marketing and service quality have a positive and significant influence on customer loyalty, while servicescape has a positive but insignificant influence. These findings indicate that customer loyalty is not only influenced by the physical conditions of the café environment but is more strongly influenced by customers' perceptions of the café's environmental efforts and the quality of service provided. This study has implications for business practitioners, particularly in the café industry, to focus on environmentally conscious marketing strategies and improve service quality as efforts to maintain customer loyalty. Keywords: Green Marketing, Servicescape, Service Quality, Customer Loyalty, Retrorika, Batu City.